MENGGUNAKAN STRATEGI ROLE PLAY UNTUK MENINGKATKAN KEMAMPUAN BELAJAR GEOGRAFI PADA POKOK BAHASAN CUACA DAN IKLIM UNTUK SISWA KELAS X.5 SMA NEGERI 1 SALO - Yunialis, Yunialis (UIR Press, 2014)
This was a Classroom action research which focused on improving students’ ability in studying Geography in weather and climates. Based on the observation of the researcherat class X SMA Negeri 1 Salo found some problemsespecially in the classroom X.5. Most students did not understand the material being taughtby the teachers. Observations that have been made with giving 25 questions in the form of essays, student got difficulties in understanding the material. 86% students made mistakes in answering questions. Their score below 75, so they did not reach the minimum completeness criteria (KKM); over 75. Only 14% students were able to answer questions.Their difficulty in answering the question because they were not full attention when learning in the classroom.The reseacher solved the problem by using role play in this subject then after cycle 1, the result of the average value of students increased to 67.71. This means the ability to learn geography on the subject of weather and climate for the students at the level of 61-80 ability (good), but has not reached the standard minimum completeness criteria (KKM) yet; above 75.In cycle 2, the result of the average value of students increased to be 78.86. It means being able to read the text of the students were at the level of 61-80 ability (good). This value was higher than the standard minimum completeness criteria (KKM); over 75